Zakat dan Ketimpangan Pendapatan: Analisis Data BPS dan BAZNAS 2015–2024 - Rohmi Fuadi; Ubaidillah Ubaidillah; Khairul Anwar (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study aims to analyze the effectiveness of zakat in reducing income inequality in Indonesia. The data used is secondary data from the National Amil Zakat Agency (BAZNAS) and the Central Statistics Agency (BPS) for the 2015–2024 period. The research method used multiple linear regression with the Ordinary Least Squares (OLS) approach. The results showed that the distribution of zakat had a significant positive effect on the Gini Index (β = 0.0013511; p = 0.002), while the Gross Domestic Product (GDP) per capita had a significant negative effect (β = –0.0000198; p = 0.000). An Adjusted R² value of 0.91 indicates that the model has a very strong ability to explain variations in income inequality. These findings show that although the collection and distribution of zakat has increased from year to year, its impact on reducing inequality has not been optimal. This can be caused by the limited amount of zakat funds collected compared to the real needs of the community and the distribution that is not fully on target. On the other hand, economic growth reflected in the increase in GDP per capita has proven to be still the dominant factor in reducing income inequality in Indonesia. The implications of this study emphasize the importance of optimizing zakat management so that it not only functions as a philanthropic instrument, but also as a sustainable economic instrument. BAZNAS and related institutions are expected to be able to strengthen the zakat distribution system through productive economic empowerment programs, so that zakat can make a real contribution in reducing inequality and supporting more inclusive development in Indonesia.